Waste waters from copper ores mining/flotation in ‘Bucbim’ mine: characterization and remediation - Svetomir Hadži Jordanov, Mirjana Maletic, Aleksandar Dimitrov, Dragan Slavkov, Perica Paunovic (Elsevier, 2007)
Open pit mining, ore dressing and flotation in Bucbim mine are accomplished by using vast amount of water. A complex water circulation scheme is employed, and this one is necessarily accompanied by water losses. In this process, part of the flotation waste water enters the nearby watercourses, thus contaminating them with heavy metals, organic tensides, etc. Resulting contamination is further spread up to the Vardar River and Aegean Sea. Smaller part of the ponds (and other out-of-pipe) water reaches the underground aquifers and lowers the quality of water used in nearby villages wells. Acid mine leaching of copper minerals in the overburden disposal site as well as mine waters also contribute in stream pollution. The waste waters from overburden leaching are extremely concentrated and contain up to 840 mg/L Cu2+ and 360 mg/L Mn2+, in an average flow of 2 L/s.